2007
DOI: 10.1002/chin.200719205
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Ordering Phenomena in D‐ and F‐Electron Systems

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 253 publications
(415 reference statements)
0
10
0
Order By: Relevance
“…Also in 4d materials spin-orbital physics plays a role [61], as for instance in Ca 2−x Sr x RuO 4 systems with Ru 4+ ions in 4d 4 configuration [62][63][64][65][66]. Recently it has been shown that unconventional magnetism is possible for Ru 4+ and similar ions where spin-orbit coupling plaus a role [67,68].…”
Section: Introductionmentioning
confidence: 99%
“…Also in 4d materials spin-orbital physics plays a role [61], as for instance in Ca 2−x Sr x RuO 4 systems with Ru 4+ ions in 4d 4 configuration [62][63][64][65][66]. Recently it has been shown that unconventional magnetism is possible for Ru 4+ and similar ions where spin-orbit coupling plaus a role [67,68].…”
Section: Introductionmentioning
confidence: 99%
“…
1 Solids with strong electron correlations generally develop exotic phases of electron matter at low temperatures [1,2,3,4,5]. Among such systems, the heavyfermion semi-metal URu 2 Si 2 presents an enigmatic transition at T o = 17.5 K to a 'hidden order' state whose order parameter remains unknown after 23 years of intense research [6,7].
…”
mentioning
confidence: 99%
“…As pointed in many papers on oxides 38 , the effective Hamiltonian for obtaining the phase diagram is given by: In the above equation, the electron-phonon coupling term contains breathing mode and Jahn-Teller modes (i.e., modes corresponding to optical phonons) because they correspond to the dominant electron-phonon interactions. Here, since we deal with a single e g electron, the electron-electron-interaction term is not relevant.…”
Section: Discussionmentioning
confidence: 99%